E-modul berbasis Android dalam mendukung aktivitas belajar mandiri peserta didik (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2022)
This study describes how students’ independent learning activities with Android-based E-Module media. Independent learning becomes an urgency when the PJJ and PTMT systems are implemented. In this regard, of course, learning media is needed that can support the growth of independent learning attitudes. Based on journal literacy and previous research, the Android-based E-Module media is one of the media that can be used by students to do independent learning so that the essence and goals of learning can be achieved. This study aims to provide an overview of Android-based E-Modules and describe students’ independent learning activities with Android-based E-Modules media. The method used is descriptive qualitative. The subjects of this study used purposive sampling, namely students in class XI MIPA 2 SMA Pasundan 2 Bandung. Data collection techniques used are observation, interviews and documentation studies. The findings and results of the study show that the Android-based E-Modul media supports independent learning which can be seen from the students’ independent learning activities using Android-based E-Module media.Android
Keywords: Android; E-Modul; Independent Learning; PJJ; PTMT